2022
DOI: 10.4103/1673-5374.332131
|View full text |Cite
|
Sign up to set email alerts
|

Construction and imaging of a neurovascular unit model

Abstract: In 2001, the concept of the neurovascular unit was introduced at the Stroke Progress Review Group meeting. The neurovascular unit is an important element of the health and disease status of blood vessels and nerves in the central nervous system. Since then, the neurovascular unit has attracted increasing interest from research teams, who have contributed greatly to the prevention, treatment, and prognosis of stroke and neurodegenerative diseases. However, additional research is needed to establish an efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 181 publications
0
12
0
Order By: Relevance
“…The neurovascular unit is an important element of the health and disease status of blood vessels and nerves in the central nervous system, which consists of neurons, nerve glia cells (astrocytes, microglia, oligodendrocytes), vascular cells (brain microvascular endothelial cells (BMECs), pericytes, and smooth muscle cells (SMCs)), and brain-specific extracellular matrix (ECM). BMECs line the capillaries of the brain, form densely arranged tight junctions with pericytes, and form the brain’s unique barrier structure, the blood–brain barrier (BBB) . The BBB is a complex network essential for the normal functioning of the brain, which impedes the influx of most foreign substances from the blood to the brain to keep a constant brain environment. , The BBB is generally composed of five constituent parts, namely the pericytes, astrocytes, neurons, basement membrane, BMECs, and tight junctions. Pericytes are wrapped around the brain capillaries, which are responsible for the regulation of the blood flow in the brain capillary through contraction and relaxation; they physiologically control cerebral blood flow and limit blood flow after ischemia by constricting capillaries and subsequently dying. , Astrocytes have significant functions in brain metabolism, allowing cellular interaction with the neurons surrounding the BBB. , Brain microvascular endothelial cells are the main structure of the BBB, which severely restrict the diffusion of approximately 98% small molecules and nearly 100% large molecules such as peptides and proteins into the brain. , …”
Section: Blood–brain Barrier and Blood–brain-tumor Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…The neurovascular unit is an important element of the health and disease status of blood vessels and nerves in the central nervous system, which consists of neurons, nerve glia cells (astrocytes, microglia, oligodendrocytes), vascular cells (brain microvascular endothelial cells (BMECs), pericytes, and smooth muscle cells (SMCs)), and brain-specific extracellular matrix (ECM). BMECs line the capillaries of the brain, form densely arranged tight junctions with pericytes, and form the brain’s unique barrier structure, the blood–brain barrier (BBB) . The BBB is a complex network essential for the normal functioning of the brain, which impedes the influx of most foreign substances from the blood to the brain to keep a constant brain environment. , The BBB is generally composed of five constituent parts, namely the pericytes, astrocytes, neurons, basement membrane, BMECs, and tight junctions. Pericytes are wrapped around the brain capillaries, which are responsible for the regulation of the blood flow in the brain capillary through contraction and relaxation; they physiologically control cerebral blood flow and limit blood flow after ischemia by constricting capillaries and subsequently dying. , Astrocytes have significant functions in brain metabolism, allowing cellular interaction with the neurons surrounding the BBB. , Brain microvascular endothelial cells are the main structure of the BBB, which severely restrict the diffusion of approximately 98% small molecules and nearly 100% large molecules such as peptides and proteins into the brain. , …”
Section: Blood–brain Barrier and Blood–brain-tumor Barriermentioning
confidence: 99%
“…BMECs line the capillaries of the brain, form densely arranged tight junctions with pericytes, and form the brain's unique barrier structure, the blood−brain barrier (BBB). 25 The BBB is a complex network essential for the normal functioning of the brain, which impedes the influx of most foreign substances from the blood to the brain to keep a constant brain environment. 26,27 The BBB is generally composed of five constituent parts, namely the pericytes, astrocytes, neurons, basement membrane, BMECs, and tight junctions.…”
Section: Blood−brain Barrier and Blood−brain-tumor Barriermentioning
confidence: 99%
“…Regeneration of the microvasculature and nerves is one of the main challenges of bone transplantation. The neurovascular unit model constructed by printing technology facilitates the observation of neurovascular units and their positive role in monitoring and investigating the mechanisms of various central nervous system diseases (Dong et al, 2022). It has been reported that NIR can penetrate approximately 2.5 mm thickness of skin tissue and activate the angiogenic response.…”
Section: Print Micro Organizationmentioning
confidence: 99%
“…Since the establishment of the concept of the Neurovascular Unit (NVU) by the Stroke Progress Review Group 1 (National Institute of Health, 2001 2 ), the relationship between neural networks and vasculature has gained increased attention. The NVU is a multicellular and dynamic structure comprised of neural (neurons, astrocytes, and oligodendrocytes) and non-neural cells (mainly brain microvascular endothelial cells or BMECs, pericytes, smooth muscle cells, and microglia), supported by the basal lamina, a specialized extracellular matrix (Abbott et al, 2010 ; Muoio et al, 2014 ; Iadecola, 2017 ; Sweeney et al, 2019 ; Schaeffer and Iadecola, 2021 ; Soto-Rojas et al, 2021 ; Dong et al, 2022 ). The primary functions of the NVU include modulating vascular permeability, cerebral hyperemia, and immune response, which are essential for maintaining central nervous system function (Blanchette and Daneman, 2015 ; Liebner et al, 2018 ; Soto-Rojas et al, 2021 ; Dong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The NVU is a multicellular and dynamic structure comprised of neural (neurons, astrocytes, and oligodendrocytes) and non-neural cells (mainly brain microvascular endothelial cells or BMECs, pericytes, smooth muscle cells, and microglia), supported by the basal lamina, a specialized extracellular matrix (Abbott et al, 2010 ; Muoio et al, 2014 ; Iadecola, 2017 ; Sweeney et al, 2019 ; Schaeffer and Iadecola, 2021 ; Soto-Rojas et al, 2021 ; Dong et al, 2022 ). The primary functions of the NVU include modulating vascular permeability, cerebral hyperemia, and immune response, which are essential for maintaining central nervous system function (Blanchette and Daneman, 2015 ; Liebner et al, 2018 ; Soto-Rojas et al, 2021 ; Dong et al, 2022 ). Cerebral hyperemia allows the supply of oxygen and glucose to the nervous tissue, and, under physiological conditions, the human brain consumes about 20% of the total body circulating oxygen (Muoio et al, 2014 ; Iadecola, 2017 ; Schaeffer and Iadecola, 2021 ).…”
Section: Introductionmentioning
confidence: 99%